Third New Alkaloids from Corydalis impatiens - Chang Li, Ji; Peng Li, Gan; Hua Nie, Jian; Ju Yang, Qiu; Li, Ping; Shan Liu, Ya (Asian Journal of Chemistry, 2015)
A new alkaloids, named impatien C 1, was isolated from the roots of Corydalis impatiens (Pall.) Fisch. The structures of the new compounds were established on the basis of spectroscopic data analysis, especially of their 2D NMR spectra.